Unlocking the Therapeutic Potential of Adipose-Derived Stem Cell Secretome in Oral and Maxillofacial Medicine: A Composition-Based Perspective - Chiara Giannasi; Francesca Cadelano; Elena Della Morte; Camilla Baserga; Camilla Mazzucato; Stefania Niada; Alessandro Baj (Biology, 2024)
The adipose-derived stem cell (ADSC) secretome is widely studied for its immunomodulatory and regenerative properties, yet its potential in maxillofacial medicine remains largely underexplored. This review takes a composition-driven approach, beginning with a list of chemokines, cytokines, receptors, and inflammatory and growth factors quantified in the ADSC secretome to infer its potential applications in this medical field. First, a review of the literature confirmed the presence of 107 bioactive factors in the secretome of ADSCs or other types of mesenchymal stem cells. This list was then analyzed using the Search Tool for Retrieval of Interacting Genes/Proteins (STRING) software, revealing 844 enriched biological processes. From these, key processes were categorized into three major clinical application areas: immunoregulation (73 factors), bone regeneration (13 factors), and wound healing and soft tissue regeneration (27 factors), with several factors relevant to more than one area. The most relevant molecules were discussed in the context of existing literature to explore their therapeutic potential based on available evidence. Among these, TGFB1, IL10, and CSF2 have been shown to modulate immune and inflammatory responses, while OPG, IL6, HGF, and TIMP1 contribute to bone regeneration and tissue repair. Although the ADSC secretome holds great promise in oral and maxillofacial medicine, further research is needed to optimize its application and validate its clinical efficacy.